Tempeh as a substitute of meat protein - Serôdio, A. (2020)
According to the Portuguese Association of vegetarians, adherence to vegetarian diets, and conscience with a reduction of meat consumption is increasing in Portugal. This study aims to describe the tempeh’s protein and amino acid (aa) profile, including the impact of culinary procedures. The results will be then included on the National Food Composition Table increasing the available information in this alternative protein sources, before and after cooking. Twenty tempeh samples from six different brands and production sets, representing the varieties available for consumption in Portugal, were purchased in commercial surfaces. Each sample was analysed “raw” (as it is on the package) and after two culinary procedures, sauteed and stewed after been marinated overnight, both procedures were executed in triplicate. “Raw” and cooked samples were grouped in different pools, each one with 20 sub-samples. Each pool was analysed in triplicate for aa profile. Amino acid profile was determined by UPLC/PDA (Ultra performance liquid chromatography with photodiode array detector). After quantification of aas, the protein quality was evaluated, by the calculation of protein scores. Tempeh presents values of the sum of amino acids between 11.5g/100g in “raw”, 12.6g/100g in sauteed and 10.05g/100g in stewed samples. Glutamic acid was the aa that shows the highest value in all samples. Protein scores present values above 1 for all aa, except for leucine and sulfur aa (methionine and cysteine) that represent the limiting aa. Concerning sum of aa, values decrease significantly (p> 0.05), from salted to “raw” and stewed after marinated, respectively. The results demonstrate that the culinary method used on tempeh’s changes the protein content. The existence of limiting aa confirms that we are in the presence of a legume. Thus requires protein complementarity, a combination of cereals with legumes, to obtain all essential aa demanded in one meal. However, tempeh constitutes one valid alternative for vegetable protein choices. The presented study reveals the importance of the inclusion of these results in the Portuguese Food Composition Table.